Peripartum cardiomyopathy, a rare disease with usual manifestations: about two cases - Ospino-Guzmán, Jessica Liliana (2023)
Peripartum cardiomyopathy is a rare form of heart failure characterized by left ventricular systolic dysfunction occurring at the end of pregnancy or in the months following delivery. Its incidence is estimated at 1 in every 1 000 to 4 000 deliveries according to US registries, with a high mortality in the African population. Its exact cause is unknown, but various pathophysiological  theories have been proposed; its diagnosis is based on clinical manifestations and the exclusion of other causes of heart failure and although its prognosis is generally good, a small proportion of women may present with chronic heart failure and thromboembolic complications. We present two cases of peripartum cardiomyopathy that debuted with dyspnea and had a usual course of the disease. We highlight the diagnostic process and therapeutic plan based on the latest available guidelines according to the literature review, which favored the good clinical outcome of both patients.